Institutional mechanisms for improving the quality of life of the population in the context of the information society development - A. Zh. Panzabekova; A. E. Tazhieva; G. B. Nurlikhina; G. N. Appakova (Экономика: стратегия и практика, 2021)
The purpose of the study is to develop institutional approaches to managing the quality of life of the population in the Republic of Kazakhstan. To achieve the goal of the study, there is carried out a theoretical and methodological substantiation of institutional mechanisms for improving the quality of life of the population in the work. Along with indicators for assessing the effectiveness of institutions, it is proposed to use additional criteria that reflect specific rules for the functioning of institutions. Institutions and their instruments of influence on the quality of life of the population are systematized. At the same time, the main attention in the article is paid to the study of the role of the state in regulating the quality of life of the population. The components of the system of state regulation of the quality of life are shown, its main mechanisms are described. To assess the social policy in the field of improving the quality of life of the population, an analysis of state programs and strategies was carried out. To fill the identified «gaps», proposals, priorities and prerequisites of institutional mechanisms for improving the quality of life of the population of Kazakhstan, adapted to modern conditions, were developed and substantiated.The results of the study can be used by the relevant government bodies in the process of improving legislation in the field of implementing the social policy of the Republic of Kazakhstan, as well as by scientists, doctoral students and undergraduates engaged in researching the problems of improving the quality of life in Kazakhstan.